Characterization of Three Species of Thrips on Weeping Fig, Nutmeg, and Marine Seruni Plants Based on Mtcoi DNA Sequences - Nia Kurniawaty; Purnama Hidayat; Aunu Rauf (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Thrips are widely reported as pests in vegetable crops. However, the existence of Phlaeothripidae members has a less concern in Indonesia. Phlaeothripidae is the only family of Tubulifera Suborder and some reports suggested that they had potential to be pests in several crops due to their ability to roll up and to make galls on leaves. The first step in pest management attempt is to identify the pest accurately and quickly, so the pest management can be on target and more efficient. One of the identification methods is the molecular identification using DNA barcoding techniques. This study aimed to characterize and to compare species thrips in banyan, nutmeg, and marine seruni based on their molecular characteristics. This research was conducted in Bogor and Kuningan. The process of molecular characterization consisteds of four steps DNA total extraction, amplification by using PCR, COI gene sequence, and data analysis. PCR programme was succesfully to amplified mtCOI gene fragment at 710 bp. The length of mtCOI gene of Gynaikothrips uzeli, Haplothrips ganglbaueri, and Pseudophilothrips ichini were 704, 686, and 702 bp dominated by A and T bases with nucleotide variation value of 27.8%. This results confirmed that molecular characterization using mtCOI gene mitochondrial had successfully supported the morphological data. How to CiteKurniawaty, N., Hidayat, P. Rauf, A. (2016). Characterization of Three Species of Thrips on Banyan, Nutmeg, and Marine Seruni Plants Based on Coi Gene. Biosaintifika: Journal of Biology Biology Education, 8(2), 185-192.